THE ROLE OF ARTIFICIAL INTELLIGENCE IN THE ECONOMY (Modern education and development, 2025)
Artificial intelligence is revolutionizing the ekonomy industry by enhancing content creation, distribution, and consumption processes. AI technologies, including machine learning, natural language processing, and computer vision, have made significant strides in improving automation, personalizing user experiences, and optimizing operations. This paper explores the transformative role of AI in ekonomy, focusing on its applications in content recommendation, live ekonomy, news generation, and audience analysis. We examine the impact of AI on production workflows, its potential for creating more engaging content, and its ability to improve decision-making for broadcasters and advertisers.